Non-crosslinked insulating cable
Patent Information
- Application Number
- KR1020210151278
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-20
- Filing Date
- 2021-11-05
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2041-11-05
Smart Images

Figure 112021127771259-PAT00010_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a non-crosslinked insulated cable. Specifically, the present invention relates to a non-crosslinked insulated cable that is recyclable and environmentally friendly, simultaneously satisfies heat resistance, electrical properties, mechanical properties, flame retardancy, extrudability, etc., and simultaneously improves the structural stability of the cable, cable laying properties, insulation end stripping workability, and ease of winding for storage. Background Technology
[0002] Low-voltage cables used for general electrical constructions, wiring of electrical equipment, or indoor wiring may include a conductor and an insulating layer surrounding it. Although the insulating layer material was previously made by mixing non-crosslinked polyvinyl chloride (PVC) resin and non-crosslinked polyolefin (PO) resin for recycling purposes, there was a problem with the leakage of toxic gases harmful to the human body in the event of a fire. Furthermore, when using conventional crosslinking extrusion tools during the non-crosslinking extrusion of the insulating layer, it was difficult to control the adhesion between the conductor and the insulating layer, resulting in a significant decrease in the structural stability of the cable or the workability of stripping the ends of the insulating layer for cable installation.
[0003] Therefore, conventional low-voltage cables generally used cross-linked polyolefin (PO) resin as the insulation layer material; however, since cross-linked polyolefin (PO) resin is in a cross-linked form, when the lifespan of a cable containing an insulation layer manufactured from an insulation composition containing it ends, the resin constituting the insulation layer cannot be recycled and must be disposed of by incineration, making it unenvironmentally friendly.
[0004] Meanwhile, indoor wiring cables for lighting, heating, etc., are installed in a non-exposed manner by being introduced into the interior of the ceiling, wall, floor, etc., at a specific point and then pulled out at a certain distance from said specific point; in this case, the cable introduced into the interior of the ceiling, wall, floor, etc., is transported through a conduit made of a material such as PVC, which protects it and guides it until it is pulled out.
[0005] If a cable being transported through the aforementioned conduit exhibits excessive flexibility or stiffness, it may be difficult to transport, and transport may also be difficult due to friction with the inner wall of the conduit or with other cables inserted together. In particular, transport may be even more difficult if the cable is transported through the conduit in curved areas resulting from the structure of a building or facility, such as the ceiling, walls, or floor.
[0006] Therefore, while the cable possesses appropriate flexibility and rigidity for transport, it is necessary for the surface friction coefficient of the insulation layer constituting the cable to be sufficiently low to improve cable laying performance by minimizing friction with the wire, the inner wall of the conduit, or other cables transported together. However, if the surface friction coefficient of the insulation layer is excessively low, a predetermined frictional force between cables is not secured when the cable is wound into a bundle for storage, causing the cable to unravel and making storage difficult. Consequently, there is an urgent need for a non-crosslinked insulated cable that is recyclable and environmentally friendly, simultaneously satisfies heat resistance, electrical properties, mechanical properties, flame retardancy, and extrudability, and simultaneously improves structural stability, cable laying performance, ease of stripping the insulation end, and ease of winding for storage. The problem to be solved
[0007] The present invention aims to provide a non-crosslinked insulated cable that is recyclable and environmentally friendly, and simultaneously satisfies heat resistance, electrical properties, mechanical properties, flame retardancy, extrudability, etc.
[0008] In addition, the present invention aims to provide a non-crosslinked insulated cable in which the structural stability, cable laying ability, insulation end stripping workability, and ease of winding for storage are simultaneously improved. means of solving the problem
[0009] To solve the above problem, the present invention,
[0010] A non-crosslinked insulated cable comprising a conductor and an insulating layer surrounding the conductor, wherein the insulating composition forming the insulating layer comprises, as a base resin, a polypropylene, an ethylene copolymer, and a polyolefin resin grafted with maleic anhydride, and wherein the peak fraction of the propylene monomer according to the following mathematical formula 1 is 0.35 to 0.55, and
[0011] [Mathematical Formula 1]
[0012] Peak fraction = CH3 absorption rate peak value / CH2 and CH3 absorption rate peak value
[0013] In the above mathematical formula 1,
[0014] The above CH3 absorption peak value is a wavenumber of 1376 cm⁻¹, which represents propylene monomer during FT-IR analysis of the insulating layer. -1 It is the peak value of the absorption rate present in, and the CH2 and CH3 absorption rate peak values represent wavenumber 1465 cm⁻¹, which corresponds to ethylene monomer and propylene monomer, respectively, during FT-IR analysis of the insulating layer. -1 It is the peak value of the absorption rate existing in, and the peak value of the absorption rate is a wavenumber of 1700 to 1500 cm -1 The lowest point between and 1300 to 1100 cm -1A non-crosslinked insulating cable is provided, based on a baseline which is a line connecting the lowest points between them, and has a stripping force of 1 to 8.5 kgf, which is the minimum force for stripping the insulating layer from the conductor.
[0015] Herein, the insulating layer is extruded at an extrusion die temperature of 145°C or higher and an extrusion line speed of 150 mpm or higher, thereby providing a non-crosslinked insulating cable.
[0016] In addition, a non-crosslinked insulating cable is provided, characterized in that the conductor is preheated to 115°C or higher before the extrusion of the insulating layer.
[0017] Meanwhile, the present invention provides a non-crosslinked insulated cable characterized by having six curved sections with rounded corners and bent at right angles, and having a shape having said curved sections, inserted into a PVC corrugated tube having a vertical length of 1 m, a horizontal length of 9 m, and an inner diameter of 16 mm, and having three strands of said non-crosslinked insulated cable including a 2.5 SQ single conductor and an insulating layer with a thickness of 0.8 mm, wherein the average tensile force required when pulling out the cable from a vertically upward 45° direction from one end of the PVC corrugated tube is 2 to 5 kgf.
[0018] Meanwhile, the above insulating composition provides a non-crosslinked insulating cable that includes a flame retardant, has a melt flow index (MRF) of 20 to 26 g / 10 min (190°C, 21.6 kg), and a minimum point torque (ML) (190°C) of 1.1 to 1.4 lb-in.
[0019] Herein, a non-crosslinked insulated cable is provided, characterized in that the relationship between the melt flow index (MFR) and the lowest point torque (ML) satisfies the following mathematical formula 4.
[0020] [Mathematical Formula 4]
[0021]
[0022] In addition, the present invention provides a non-crosslinked insulating cable characterized in that the polypropylene resin comprises a propylene block copolymer having a melting point of 150 to 170°C, the ethylene copolymer comprises two types of polyolefin elastomers (POE) having melting points of 60 to 100°C and different melting points from each other, and the maleic anhydride-grafted polyolefin resin comprises a maleic anhydride-grafted polyolefin elastomer having a melting point of 70 to 90°C.
[0023] Herein, the ethylene copolymer comprises a low-melting point polyolefin elastomer (POE) with a melting point of 60 to 70°C and a high-melting point polyolefin elastomer (POE) with a melting point of 75 to 100°C, thereby providing a non-crosslinked insulating cable.
[0024] In addition, based on 100 parts by weight of the base resin, the content of the polypropylene resin is 20 to 45 parts by weight, the content of the ethylene copolymer is 30 to 70 parts by weight, and the content of the maleic anhydride-grafted polyolefin resin is 10 to 25 parts by weight, thereby providing a non-crosslinked insulating cable.
[0025] In addition, based on 100 parts by weight of the base resin, the content of the polypropylene resin is 25 to 45 parts by weight, the content of the ethylene copolymer is 30 to 55 parts by weight, and the content of the maleic anhydride-grafted polyolefin resin is 10 to 25 parts by weight, and the insulating composition further comprises 2.5 to 3.5 parts by weight of a lubricant based on 100 parts by weight of the base resin, thereby providing a non-crosslinked insulating cable.
[0026] Herein, the present invention provides a non-crosslinked insulating cable characterized by comprising one or more types selected from the group consisting of stearic acid-based lubricants, polyethylene wax-based lubricants, and silicone-based lubricants in the form of masterbatch.
[0027] In addition, the above high-melting-point polyolefin elastomer (POE) and the above low-melting-point polyolefin elastomer (POE) provide a non-crosslinked insulated cable characterized by satisfying the following mathematical formulas 2 and 3.
[0028] [Mathematical Formula 2]
[0029]
[0030] [Mathematical Formula 3]
[0031]
[0032] In the above mathematical formulas 2 and 3,
[0033] x1, MI1, and Tm1 are the content (g), melt index (g / 10min), and melting point (°C) of the high-melting-point polyolefin elastomer, respectively, and
[0034] x2, MI2, and Tm2 are the content (g), melt index (g / 10 min), and melting point (°C) of the low-melting point polyolefin elastomer, respectively.
[0035] Furthermore, the present invention provides a non-crosslinked insulating cable characterized in that the flame retardant comprises a metal hydroxide flame retardant and a nitrogen-based flame retardant aid.
[0036] Herein, a non-crosslinked insulated cable is provided, characterized in that the nitrogen-based flame retardant aid comprises melamine cyanurate.
[0037] In addition, a non-crosslinked insulating cable is provided, characterized in that, based on 100 parts by weight of the base resin, the content of the metal hydroxide flame retardant is 150 to 190 parts by weight, and based on the total weight of the insulating composition, the content of the nitrogen-based flame retardant aid is 5 to 20% by weight.
[0038] In addition, the above insulating composition provides a non-crosslinked insulating cable characterized by including 1 to 20 parts by weight of calcium carbonate (CaCO3) as a filler based on 100 parts by weight of the base resin.
[0039] Herein, a non-crosslinked insulating cable is provided, characterized in that, based on 100 parts by weight of the base resin, the total content of the flame retardant and the filler is 150 to 200 parts by weight.
[0040] In addition, the insulating composition comprises 0.1 to 10 parts by weight of other additives based on 100 parts by weight of the base resin, and the other additives comprise one or more selected from the group consisting of antioxidants, hygroscopic agents, processing stabilizers, and pigments, thereby providing a non-crosslinked insulating cable. Effects of the invention
[0041] The non-crosslinked insulating cable according to the present invention is environmentally friendly by applying a non-crosslinked type insulating layer, and exhibits excellent effects that simultaneously satisfy heat resistance, electrical properties, mechanical properties, flame retardancy, extrudability, etc. through a novel combination of base resin and additives of the insulating composition forming the insulating layer.
[0042] In addition, the non-crosslinked insulated cable according to the present invention exhibits an excellent effect in which the structural stability of the cable and the workability of stripping the end of the insulated layer for cable installation are simultaneously improved by precisely controlling the adhesion force between the conductor and the insulated layer through a change in the process conditions of the insulated layer extrusion process.
[0043] Furthermore, the non-crosslinked insulating cable according to the present invention exhibits excellent effects in that the cable laying performance is improved and the ease of winding for storage is improved by precisely controlling the surface friction coefficient of the insulating layer through the control of the base resin constituting the insulating layer and the application of a lubricant. Brief explanation of the drawing
[0044] Figure 1 schematically illustrates the cross-sectional structure of a non-crosslinked insulating cable according to the present invention. FIG. 2 schematically illustrates the appearance of an insulation layer stripping force measuring device for a non-crosslinked insulated cable according to the present invention. Figure 3 schematically illustrates a cross-sectional view of an insulation layer extrusion die of a non-crosslinked insulating cable according to the present invention. FIG. 4 schematically illustrates a virtual laying environment for evaluating the laying performance of a non-crosslinked insulating cable according to the present invention. Figure 5 is an example of a graph of FT-IR analysis results for an insulating layer in a non-crosslinked insulating cable according to the present invention. Specific details for implementing the invention
[0045] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete, and to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art. Throughout the specification, the same reference numerals indicate the same components.
[0046] Figure 1 schematically illustrates the cross-sectional structure of a non-crosslinked insulating cable according to the present invention.
[0047] As illustrated in FIG. 1, the non-crosslinked insulating cable according to the present invention may include a conductor (100) and an insulating layer (200) surrounding the conductor (100). The conductor (100) may be made of a conductive material capable of carrying current, such as a metal like copper or aluminum, and may be a single wire or a stranded wire formed by combining multiple wires. The diameter may be appropriately selected according to the capacity of the cable including the same.
[0048] The insulating layer (200) may be formed from a non-crosslinked extrusion of an insulating composition including a base resin, a flame retardant, a filler, a lubricant, and other additives, and the stripping force, which is the minimum force required to strip the insulating layer (200) from the conductor (100), may be 1 to 8.5 kgf, preferably 3 to 5 kgf.
[0049] If the above stripping force is less than 1 kgf, the adhesion force formed between the conductor (100) and the insulation layer (200) during the non-crosslinked extrusion of the insulation layer (200) is insufficient, so the conductor (100) and the insulation layer (200) are separated too easily in the non-crosslinked insulation cable, and the structural stability of the cable may be significantly reduced.
[0050] On the other hand, if the stripping force exceeds 8.5 kgf, the adhesion force formed between the conductor (100) and the insulation layer (200) is excessive, making it difficult to strip the insulation layer at the end of the cable for laying the cable, and problems such as insulation material remaining on the surface of the conductor after stripping may occur.
[0051] FIG. 2 schematically illustrates the appearance of an insulation layer stripping force measuring device for a non-crosslinked insulated cable according to the present invention.
[0052] As illustrated in FIG. 2, the stripping force of the insulation layer of a non-crosslinked insulated cable according to the present invention can be measured using a Universal Testing Machine (UTM). For example, after stripping the insulation layer for a length of 3 cm from one end of a cable specimen with a length of 13 cm, the conductor with the stripped insulation layer is placed inside a holder equipped with an upper hole having a diameter larger than the conductor diameter and smaller than the cable outer diameter, with the conductor penetrating the upper hole being fixed to the upper grip of the UTM and the lower part of the holder being fixed to the lower grip of the UTM, and then the lower grip of the UTM is pulled downward at a speed of 150 mm / min, the force at the moment the insulation layer is stripped from the conductor, i.e., the stripping force, can be measured.
[0053] The precise controlled stripping force described above in the non-crosslinked insulating cable according to the present invention can be achieved, for example, by changing the process conditions of the non-crosslinked extrusion process of the insulating layer (200).
[0054] Figure 3 schematically illustrates a cross-sectional view of an insulation layer extrusion die of a non-crosslinked insulating cable according to the present invention.
[0055] As illustrated in FIG. 3, the insulation layer extrusion die of a non-crosslinked insulating cable according to the present invention may include a nipple (10) for fixing and transporting a conductor and a die (20) provided on the outside of the nipple (10) for forming a flow path (F) of an insulating composition extruded onto the conductor. In particular, the length (L) of the die land between the nipple tip (11) from which the conductor is discharged from the nipple (10) and the die tip (12) from which the cable extruded with the insulation layer is drawn out from the die (20) is designed to be 8 to 12 times the inner diameter of the nipple (10), which is the outer diameter of the conductor. The flow path angle (θ1), which is the angle at which the flow path (F) of the insulating composition is tilted with respect to the conductor centerline (C), is 25 to 50°, and the die land angle (θ2), which is the angle at which the inner wall of the die (12) is tilted with respect to the conductor centerline (C), is 4 to 10°.
[0056] When extruding an insulating layer using such a double-angle die, the contact distance between the conductor and the insulating composition during extrusion is increased, and the load received by the insulating composition is increased, thereby allowing the adhesion force of the insulating layer to the conductor to be precisely controlled.
[0057] Specifically, when the insulating layer (200) is formed through an extrusion die as shown in FIG. 3 with an extrusion die temperature of 145°C or higher, for example, 145 to 190°C and an extrusion line speed of 150 mpm or higher, for example, 150 to 500 mpm, the stripping force of the previously described numerical range can be achieved without eccentricity of the conductor (100), and preferably, the conductor can be preheated to 115°C or higher, for example, 115 to 145°C, before performing non-crosslinked extrusion of the insulating layer.
[0058] FIG. 4 schematically illustrates a virtual laying environment for evaluating the laying performance of a non-halogen flame-retardant polyolefin insulated wire according to the present invention. As shown in FIG. 4, the virtual laying environment is composed of a PVC corrugated pipe having a vertical length of 1 m, a horizontal length of 9 m, and an inner diameter of 16 mm, having six curved sections with rounded corners and right-angled sections, and the laying performance of the non-crosslinked insulated cable can be evaluated by repeatedly measuring the tensile force required when pulling out three strands of a non-crosslinked insulated cable inserted into the PVC corrugated pipe and including a 2.5 SQ single conductor and an insulation layer with a thickness of 0.8 mm using a push-pull gauge at a vertical upward 45° direction from one end of the PVC corrugated pipe, and calculating the average value.
[0059] Here, the tensile force may be 2 to 5 kgf, and if the tensile force exceeds 5 kgf, the laying ability of the cable is significantly reduced, whereas if the tensile force is less than 2 kgf, the surface friction coefficient of the cable insulation layer is excessively low, making it difficult to wind the cable for storage.
[0060] Meanwhile, the base resin of the insulating composition forming the insulating layer (200) may include polypropylene resin, ethylene copolymer, and a polyolefin resin grafted with maleic anhydride.
[0061] Here, the base resin is controlled such that the peak fraction of the propylene monomer according to the following mathematical formula 1 is 0.35 to 0.55, thereby controlling the tensile strength and stripping strength of the insulation layer, which improves the laying ability and winding ease of the cable, while simultaneously improving structural stability.
[0062] [Mathematical Formula 1]
[0063] Peak fraction = CH3 absorption rate peak value / CH2 and CH3 absorption rate peak value
[0064] In the above mathematical formula 1,
[0065] The above CH3 absorption peak value is a wavenumber of 1376 cm⁻¹, which represents propylene monomer during FT-IR analysis of the insulating layer. -1 It is the peak value of the absorption rate present in, and
[0066] The above CH2 and CH3 absorption rate peak values represent wavenumber 1465 cm⁻¹, which corresponds to ethylene monomer and propylene monomer, respectively, during FT-IR analysis of the insulating layer. -1 It is the peak value of the absorption rate present in, and
[0067] The peak value of the above absorption rate is a wavenumber of 1700 to 1500 cm⁻¹, as shown in FIG. 5. -1 The lowest point between and 1300 to 1100 cm -1 Based on the baseline, which is the line connecting the lowest points in between, the peak value of the CH3 absorption rate in the graph of Fig. 5 is wavenumber 1376 cm⁻¹ -1 It is the difference between the peak value of the absorption rate present (PEAK #2) and the y-value of the baseline at the corresponding wavenumber, and the above CH2 and CH3 absorption rate peak values are at wavenumber 1465 cm⁻¹ -1 It is the difference between the peak value of the absorption rate present in (PEAK #1) and the y value of the baseline at the corresponding wavenumber.
[0068] Specifically, if the peak fraction is less than 0.35, the tensile strength of the insulation layer increases, which may reduce the ease of laying and winding of the cable, whereas if the peak fraction is greater than 0.55, the structural stability of the cable may decrease due to a decrease in the stripping force of the insulation layer against the conductor.
[0069] The above polypropylene resin may have a melting point of 150 to 170°C. Here, if the melting point of the polypropylene resin is less than 150°C, the heat resistance of the insulating composition may be significantly reduced, whereas if it is greater than 170°C, the elongation rate, extrudability, etc. of the insulating composition may be reduced.
[0070] The above polypropylene resin may comprise, for example, a propylene homopolymer and / or a propylene copolymer, and preferably comprises a propylene monomer and C of ethylene and 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, etc. 4-12 It may include a propylene block copolymer formed by copolymerizing one or more comonomers selected from the group consisting of alpha-olefins.
[0071] The above polypropylene resin can be polymerized under a conventional stereo-specific Ziegler-Natta catalyst, a metallocene catalyst, a confined geometric catalyst, or other organometallic or coordination catalyst, and preferably under a Ziegler-Natta catalyst or a metallocene catalyst.
[0072] Here, the metallocene is a general term for bis(cyclopentidenyl) metals, which are new organometallic compounds in which cyclopentadiene and a transition metal are combined in a sandwich structure, and the general formula of the simplest structure is M(C5H5)2 (where M is Ti, V, Cr, Fe, Co, Ni, Ru, Zr, Hf, etc.).
[0073] Since the polypropylene resin polymerized under the above metallocene catalyst has a low catalyst residue of about 200 to 700 ppm, it is possible to suppress or minimize the degradation of the electrical properties of the insulating composition containing the polypropylene resin due to the catalyst residue.
[0074] The above ethylene copolymer may include two types of polyolefin elastomers (POE) with different melting points, and the polyolefin elastomer (POE) has excellent compatibility with the polypropylene resin, and in particular, has a lower degree of crystallinity compared to the polypropylene resin, so it has excellent loading ability with additives such as flame retardants, so even when a large amount of flame retardant is added to the insulation layer, flame retardancy can be improved by uniform dispersion of the flame retardant, while avoiding or minimizing the degradation of mechanical properties, flexibility, etc.
[0075] The above two types of polyolefin elastomers (POE) may include, for example, a low-melting-point polyolefin elastomer (POE) with a melting point of 60 to 70°C and a high-melting-point polyolefin elastomer (POE) with a melting point of 75 to 100°C.
[0076] Here, if the melting point of the low melting point polyolefin elastomer (POE) is less than 60°C, the heat resistance of the insulating composition may be reduced, whereas if the melting point of the high melting point polyolefin elastomer (POE) is greater than 100°C, the extrudability of the insulating composition may be reduced and the compatibility between the insulating composition and additives such as flame retardants may be reduced.
[0077] The above high-melting-point polyolefin elastomer (POE) and the above low-melting-point polyolefin elastomer (POE) can simultaneously satisfy the relationships in Equations 2 and 3 below.
[0078] [Mathematical Formula 2]
[0079]
[0080] [Mathematical Formula 3]
[0081]
[0082] In the above mathematical formulas 2 and 3,
[0083] x1, MI1, and Tm1 are the content (g), melt index (g / 10min), and melting point (°C) of the high-melting-point polyolefin elastomer, respectively, and
[0084] x2, MI2, and Tm2 are the content (g), melt index (g / 10 min), and melting point (°C) of the low-melting point polyolefin elastomer, respectively.
[0085] The above mathematical formula 2 represents the relationship between the content, melt index, and melting point of high-melting-point polyolefin elastomers and low-melting-point polyolefin elastomers. It implies that even if a polyolefin elastomer with a high melting point is included within a certain range, if the melt index (MI) of the high-melting-point polyolefin elastomer is within a certain range, the physical properties such as extrudability, electrical and mechanical properties of the entire insulating composition can be satisfied.
[0086] Meanwhile, the above mathematical formula 3 is a formula representing the correlation between the melting point and content of high-melting-point polyolefin elastomers and low-melting-point polyolefin elastomers, and implies that the content of low-melting-point resin must be guaranteed to some extent because if the content of high-melting-point resin is too high, filler loading ability decreases, which can lead to a deterioration of physical properties such as processability and mechanical properties.
[0087] Thus, the insulating composition can simultaneously improve flame retardancy, mechanical properties, and flexibility, which are in a conflicting relationship.
[0088] The maleic anhydride-grafted polyolefin resin may have a melting point of 70 to 90°C and may include, for example, a maleic anhydride-grafted polyolefin elastomer, and by further improving compatibility with additives such as flame retardants included in the insulation composition, even when a large amount of flame retardant is added to the insulation layer, flame retardancy can be improved through the uniform dispersion of the flame retardant, while simultaneously further improving mechanical properties, flexibility, etc.
[0089] Here, if the melting point of the polyolefin resin grafted with the maleic anhydride is less than 70°C, the heat resistance of the insulating composition may be insufficient, whereas if it is greater than 90°C, the compatibility with additives such as flame retardants may be insufficient.
[0090] In particular, assuming that the above insulating composition includes a specific base resin of the non-crosslinked type described above, when the melting flow rate (MFR) is controlled to 20 to 26 g / 10 min (190°C, 21.6 kg) and the melting level (ML) (190°C) is controlled to 1.1 to 1.4 lb-in, preferably when the relationship between the melting flow rate (MFR) and the melting level (ML) satisfies the following Equation 4, the physical properties do not deteriorate below the standard even when adding a flame retardant content to achieve the desired flame retardancy while satisfying the electrical properties, mechanical properties, extrudability, etc. required for the insulating layer of a low-voltage cable. Specifically, when the melting flow rate (MFR) is high, the flowability is good, and conversely, the melting level (ML) tends to be high, so they show a mutually conflicting relationship, and it has been confirmed that this relationship is as shown in the following Equation 4.
[0091] [Mathematical Formula 4]
[0092]
[0093] Here, the melt flow index (MFR) refers to the mass of an insulating composition extruded through a defined orifice within a given time under specific conditions, and in the present invention, it refers to the mass (g / 10min) of an insulating composition extruded for 10 minutes under conditions of 190°C and a 21.6 kg load.
[0094] Here, the lowest point torque (ML) is one of the values measured through a moving-die rheonmeter (MDR) facility and represents the lower limit among torque values that change over time when the composition is rotated at the same angular velocity.
[0095] Specifically, the melt flow rate (MFR) can be measured according to ASTM D1248 standards and can be obtained by filling an insulating specimen into a barrel with a capillary positioned below and an orifice formed therein, melting it, and then measuring the mass (g / 10min) of the insulating composition discharged downward through the capillary for 10 minutes when a load of 21.6 kg is applied at 190°C.
[0096] In addition, the lowest point torque (ML) can be measured using an MDR evaluation facility in accordance with ASTM D1646 standards. The MDR evaluation facility is generally used to evaluate the high-temperature crosslinking characteristics of crosslinking materials. An insulating specimen is placed between upper and lower discs, and the torque applied to the upper disc is measured while the lower disc is rotated repeatedly over a certain section at a predetermined angular velocity at 190°C. The minimum value (lb-in) among the measured torques is the lowest point torque (ML).
[0097] In particular, if the melt flow rate (MFR) of the insulating composition according to the present invention is less than 20 g / 10 min or the minimum viscous torque (ML) is greater than 1.4 lb-in, increasing the extrusion speed in accordance with the increase in the load of the insulating composition during extrusion may result in problems such as poor extrusion performance, such as the generation of bubbles in the extruded product due to internal heat generation.
[0098] Meanwhile, if the melt flow index (MFR) of the insulating composition according to the present invention exceeds 26 g / 10 min or the minimum viscosity torque (ML) is less than 1.1 lb-in, this may occur when the melting index (MI) of the base resin itself included in the insulating composition is high or when the content of processing aids such as lubricants is high. When the melting index (MI) of the base resin itself is high, a characteristic of reduced rigidity of the insulating composition may appear, and when the content of processing aids is high, problems of poor extrusion may occur, such as slip of the insulating composition within the extruder causing a decrease in extrusion volume.
[0099] For example, based on 100 parts by weight of the base resin, the content of the polypropylene resin may be 20 to 45 parts by weight, the content of the ethylene copolymer may be 30 to 70 parts by weight, and the content of the maleic anhydride-grafted polyolefin resin may be 10 to 25 parts by weight.
[0100] Furthermore, in order to satisfy not only the stripping ability of the insulation layer but also the cable laying ability, based on 100 parts by weight of the base resin, the content of the polypropylene resin may be 25 to 45 parts by weight, the content of the ethylene copolymer may be 30 to 55 parts by weight, and the content of the maleic anhydride-grafted polyolefin resin may be 10 to 25 parts by weight, and the insulation composition may additionally include 2.5 to 3.5 parts by weight of a lubricant in addition to the base resin.
[0101] Here, if the content of the polypropylene resin is below the standard, the mechanical properties, heat resistance, and heat deformation properties of the insulation layer may be reduced, and if the content of the ethylene copolymer is below the standard, the physical properties of the insulation composition, such as extrudability and electrical and mechanical properties, may be reduced, and in particular, if the content of the maleic anhydride-grafted polyolefin resin is below the standard, the coupling properties between the additive, such as a flame retardant, and the base resin may be reduced, and the overall mechanical properties and flame retardancy of the insulation composition may be reduced.
[0102] Meanwhile, if the content of the above polypropylene resin exceeds the standard, the filler loading property of the insulation composition with respect to flame retardants, etc. is insufficient, and mechanical properties such as the elongation rate of the insulation layer formed from the insulation composition may be reduced.
[0103] In addition, if the content of the ethylene copolymer exceeds the standard, the heat resistance of the insulating composition may be reduced because the melting point is relatively lower compared to the polypropylene resin, and the hardness of the insulating layer formed from the insulating composition may be reduced, increasing the possibility of reduced heat deformation characteristics, etc. In particular, if the content of the maleic anhydride-grafted polyolefin resin exceeds the standard, problems such as reduced room temperature elongation of the insulating layer and reduced workability may be caused by increased extrusion load during the extrusion of the insulating composition.
[0104] The above lubricant may include one or more selected from the group consisting of stearic acid-based lubricants, polyethylene wax-based lubricants, and silicone-based lubricants in the form of masterbatch. If the content of the above lubricant is less than 2.5 parts by weight, the frictional force between the insulating layer and the ground or the inner wall of the conduit into which the cable is inserted increases, which may significantly reduce the laying ability of the cable. On the other hand, if it exceeds 3.5 parts by weight, problems such as uneven extrusion due to a decrease in the extrusion velocity of the insulating layer and the formation of bubbles inside the insulating layer occur, and when storing the cable by winding it into a bundle, the predetermined frictional force between the cables is not secured, causing the cable winding to unravel and making storage difficult.
[0105] The above flame retardant may include non-halogenated flame retardants such as metal hydroxide flame retardants like magnesium hydroxide, aluminum hydroxide, and brucite, and nitrogen-based flame retardant adjuvants like melamine cyanurate.
[0106] However, since brucite has lower flame retardancy compared to magnesium hydroxide, aluminum hydroxide, etc., when using a mixture of brucite, it is preferable to add it in an amount of 30% by weight or less based on the total weight of the flame retardant.
[0107] As the above flame retardant, inorganic metal hydroxide particles such as magnesium hydroxide are hydrophilic with high surface energy, whereas base resins such as polypropylene are hydrophobic with low surface energy, the inorganic particles have poor dispersibility in the base resin and can impair the water resistance of the insulation layer, thereby adversely affecting electrical properties.
[0108] Therefore, in order to solve these problems, it is desirable that the surface of inorganic particles such as magnesium hydroxide be hydrophobically treated with vinylsilane, stearic acid, oleic acid, aminopolysiloxane, titanate-based coupling agents, etc.
[0109] When the above inorganic particles are surface-treated with vinylsilane, etc., the hydrolyzing groups of vinylsilane, etc. are attached to the surface of the inorganic particles, such as magnesium hydroxide, by chemically bonding through a condensation reaction, and the silane groups react with the base resin to ensure excellent dispersibility.
[0110] Based on 100 parts by weight of the base resin, the content of a metal hydroxide, particularly magnesium hydroxide, which is a flame retardant, may be 150 to 190 parts by weight, and the content of a nitrogen-based flame retardant, particularly melamine cyanurate, which is a flame retardant adjuvant, may be 5% by weight or more, for example, 5 to 20 parts by weight, based on the total weight of the insulating composition. Here, if the content of the flame retardant or the flame retardant adjuvant is below the standard, the flame retardancy of the insulating layer may be insufficient, whereas if it exceeds the standard, the extrudability, elongation rate, etc. of the insulating layer may be significantly reduced.
[0111] The above filler, i.e., the filler, is added to reduce manufacturing costs while avoiding or minimizing the degradation of the physical properties of the insulating layer, and may include, for example, calcium carbonate (CaCO3), and may be included in an amount of 1 to 20 parts by weight based on 100 parts by weight of the base resin.
[0112] Meanwhile, the total content of the flame retardant and the filler may be 150 to 200 parts by weight based on 100 parts by weight of the base resin, wherein the weight ratio of the flame retardant and the filler may be 80:20 to 100:0.
[0113] The above other additives may include antioxidants, hygroscopic agents, processing stabilizers, pigments, etc., depending on the use of the cable, and may be added in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the base resin.
[0115] [Example]
[0117] 1. Preparation Example
[0119] An insulating composition was prepared by feeding the composition and content as shown in Table 1 below into a batch-type mixer such as an internal mixer, kneader, or VIC mixer, and then generating heat above the melting point of the raw material through frictional heat by rotating a rotor. When the final temperature reached 180°C, the composition was fed into a pellet maker (product name: Feeder-ruder) and extruded under conditions of screw (170°C), cylinder (170°C), and extrusion die (200°C) to produce an insulating composition in the form of pellets. Then, an insulating layer with a thickness of 0.8 mm was extruded from this onto a 2.5 SQ single-wire conductor under conditions of cylinder (170°C) and extrusion die (180°C) to produce a cable specimen.
[0120] The type of extrusion die used in the extrusion process and the preheating conditions of the conductor before extrusion are as shown in Table 1 below. The units of the contents listed in Table 1 below are parts by weight.
[0122] Examples Comparative example 1 2 3 4 1 2 3 4 5 6 7 Suzy 1 40 35 37 35 40 40 40 50 50 30 Suzy 2 20 15 18 15 20 20 20 25 20 10 Suzy 3 60 Suzy 4 25 35 20 35 25 25 25 25 20 15 45 Suzy 5 15 15 25 15 15 15 15 15 5 15 15 flame retardant 173 173 173 173 173 173 173 123 173 173 173 lubricant 3 3 3 1.5 3 3 3 3 3 3 3 extrusion die Die 1 Die 1 Die 1 Die 1 Die 2 Die 3 Die 1 Die 2 Die 2 Die 1 Die 1 Conductor preheating (°C) 120 120 120 120 120 110 120 120 120 120 120 Peak fraction 0.38 0.46 0.35 0.45 0.37 0.38 0.38 0.37 0.36 0.32 0.56
[0123] Resin 1: Polyolefin elastomer, melting point 62°C, MI 5.0
[0124] Resin 2: Polyolefin elastomer, melting point 98°C, MI 8.0
[0125] Resin 3: Polyolefin elastomer, melting point 74℃, MI 1.0
[0126] Resin 4: Polypropylene, melting point 165℃
[0127] Resin 5: Maleic anhydride-grafted polyolefin elastomer, melting point 74°C
[0128] Flame Retardant: Silane-coated magnesium hydroxide flame retardant
[0129] Die 1: Double-angle die (Die diameter: 3.3 mm, Nipple inner diameter: 1.85 mm, Flow path angle: 30°, Die land angle: 6°, Die land length (L): 17 mm)
[0130] Die 2: Land Die (Die Diameter: 3.3 mm, Nipple Inner Diameter: 1.85 mm, Flow Angle: 30°, Die Land Angle: 0°, Die Land Length (L): 17 mm)
[0131] Die 3: Conventional die (Die diameter: 3.3 mm, Nipple inner diameter: 1.85 mm, Flow path angle: 30°, Die land angle: 0°, Die land length (L): 1 mm)
[0133] 2. Evaluation of physical properties
[0135] 1) Flame retardancy evaluation
[0136] According to standard IEC 60332-1, one cable specimen was fixed vertically from the ground, and a burner of specified standards was placed at a 45° angle to the cable specimen and a flame was applied for 60 seconds. Then, the length of the portion of the insulation layer that was not burned during natural extinguishing was measured 5 times, and the said length must be at least 50 mm from the upper indicator tape.
[0137] 2) Evaluation of molting ability
[0138] As shown in Fig. 2, after stripping the insulation layer from one end of a cable specimen with a length of 13 cm for a length of 3 cm, the conductor with the stripped insulation layer was placed inside a holder equipped with an upper hole having a diameter larger than the conductor diameter and smaller than the cable outer diameter, with the conductor penetrating the upper hole, and the conductor penetrating the upper hole was fixed to the upper grip of the UTM equipment and the lower part of the holder was fixed to the lower grip of the UTM equipment, and the force at the moment the insulation layer is stripped from the conductor, i.e., the stripping force, was measured while pulling the lower grip of the UTM equipment downward at a speed of 150 mm / min.
[0139] 3) Evaluation of Layability and Ease of Winding
[0140] In a virtual installation work environment as shown in Fig. 4, the tensile force required to pull out three strands of non-crosslinked insulated cable inserted into a PVC corrugated pipe by pulling them together using a push-pull gauge at a vertical upward 45° direction from one end of the PVC corrugated pipe was measured five times and the average value was calculated to evaluate the installability and winding ease of the non-crosslinked insulated cable.
[0141] 4) Extrudability evaluation
[0142] When extruding the insulation layer at an extrusion speed of 170 mpm, the presence or absence of abnormalities, namely the formation of bubbles inside the insulation layer and the eccentricity of the conductor, were observed visually.
[0144] The evaluation results are as shown in Table 2 below.
[0146] Examples Comparative example 1 2 3 4 1 2 3 4 5 6 7 flame retardant Good Good Good Good Good Good Good error error Good Good molting ability (kgf) 3.5 4.1 4.6 4.2 3.7 0.8 0.6 3.4 2.9 4.9 1.5 Tensile force (kgf) 7.5 3.2 6.0 8.1 7.1 7.8 8.0 9.6 10.5 9.1 3.4 Extrudability Good Good Good Good Eccentricity Good bubble generation Good Good Good Good
[0147] As described in Table 2 above, it was confirmed that the non-crosslinked insulating cable according to the example improved the structural stability and cable laying workability of the cable by controlling the adhesion between the conductor and the insulating layer through the control of the conductor's preheating and extrusion process conditions, thereby controlling the stripping force to the desired range without reducing the extrudability of the insulating layer.
[0148] However, it was confirmed that the laying ability was slightly reduced because Example 1 contained a slightly excessive amount of ethylene copolymer, Example 3 contained a slightly insufficient amount of polypropylene, and Example 4 contained a slightly small amount of lubricant.
[0149] On the other hand, it was confirmed that the non-crosslinked insulated cable of Comparative Example 1 had conductor eccentricity because the die land angle was insufficient, and the non-crosslinked insulated cable of Comparative Example 2 had significantly reduced structural stability of the cable due to the adhesion between the conductor and the insulation layer and the resulting stripping force caused by extrusion using a conventional extrusion die.
[0150] In addition, it was confirmed that the structural stability of the cable was significantly reduced because the non-crosslinked insulating cable of Comparative Example 3 had bubbles formed inside the cable insulation layer due to the unsuitability of the base resin included in the insulating composition, and the adhesion between the conductor and the insulating layer and the resulting peeling force were significantly reduced. It was also confirmed that the non-crosslinked insulating cable of Comparative Example 4 had poor flame retardancy because the flame retardant content included in the insulating composition was insufficient, and the non-crosslinked insulating cable of Comparative Example 5 had poor flame retardancy because the filler loading ability for the flame retardant was reduced due to the unsuitability of the base resin included in the insulating composition.
[0151] Furthermore, it was found that the non-crosslinked insulated cable of Comparative Example 6 had a peak fraction of the insulation layer of less than 0.35, which significantly increased the tensile strength and greatly reduced the ease of laying and winding the cable, and the non-crosslinked insulated cable of Comparative Example 7 had a peak fraction of the insulation layer of more than 0.55, which significantly reduced the stripping force of the insulation layer against the conductor and greatly reduced the structural stability of the cable.
[0152] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art may modify and change the present invention in various ways without departing from the spirit and scope of the invention as described in the claims below. Therefore, if a modified embodiment basically includes the components of the claims of the present invention, it should be considered to be included within the technical scope of the present invention. Explanation of the symbols
[0153] 100 : Conductor 200 : Insulating layer
Claims
Claim 1 A non-crosslinked insulated cable comprising a conductor and an insulating layer surrounding the conductor, wherein the insulating composition forming the insulating layer comprises, as a base resin, polypropylene comprising a propylene block copolymer having a melting point of 150 to 170°C, an ethylene copolymer comprising two types of polyolefin elastomers (POE) having melting points of 60 to 100°C and different melting points from each other, and a maleic anhydride-grafted polyolefin resin comprising a maleic anhydride-grafted polyolefin elastomer having a melting point of 70 to 90°C, wherein the insulating composition comprises a flame retardant, has a melt flow index (MFR) of 20 to 26 g / 10 min (190°C, 21.6 kg), a minimum point torque (ML) (190°C) of 1.1 to 1.4 lb-in, and wherein the base resin has a peak fraction of propylene monomer according to the following Equation 1 of 0.35 to It is 0.55, and [Equation 1] Peak fraction = CH3 absorption rate peak value / CH2 and CH3 absorption rate peak value. In the above Equation 1, the CH3 absorption rate peak value is the wavenumber 1376 cm⁻¹ representing the propylene monomer during FT-IR analysis of the insulating layer. -1 It is the peak value of the absorption rate present in, and the CH2 and CH3 absorption rate peak values represent wavenumber 1465 cm⁻¹, respectively, representing ethylene monomer and propylene monomer during FT-IR analysis of the insulating layer. -1 It is the peak value of the absorption rate existing in, and the peak value of the absorption rate is a wavenumber of 1700 to 1500 cm⁻¹ -1 The lowest point between and 1300 to 1100 cm -1 A non-crosslinked insulated cable based on a baseline, which is a line connecting the lowest points between them, and having a stripping force of 1 to 8.5 kgf, which is the minimum force for stripping the insulation layer from the conductor. Claim 2 A non-crosslinked insulated cable according to claim 1, characterized in that the average tensile force required when pulling out three strands of the non-crosslinked insulated cable, which comprises a 2.5 SQ single conductor and an insulating layer with a thickness of 0.8 mm, from a vertically upward 45° direction from one end of the PVC corrugated tube, is 2 to 5 kgf, wherein the cable has six curved sections with rounded corners and is inserted into a PVC corrugated tube having a vertical length of 1 m, a horizontal length of 9 m, and an inner diameter of 16 mm by means of the shape having said curved sections. Claim 3 delete Claim 4 A non-crosslinked insulated cable according to claim 1, characterized in that the relationship between the melt flow index (MFR) and the lowest point torque (ML) satisfies the following mathematical formula 4. [Mathematical Formula 4] Claim 5 delete Claim 6 A non-crosslinked insulated cable according to claim 1, characterized in that the ethylene copolymer comprises a low-melting-point polyolefin elastomer (POE) having a melting point of 60 to 70°C and a high-melting-point polyolefin elastomer (POE) having a melting point of 75 to 100°C. Claim 7 A non-crosslinked insulating cable according to claim 1, characterized in that, based on 100 parts by weight of the base resin, the content of the polypropylene resin is 20 to 45 parts by weight, the content of the ethylene copolymer is 30 to 70 parts by weight, and the content of the maleic anhydride-grafted polyolefin resin is 10 to 25 parts by weight. Claim 8 A non-crosslinked insulating cable according to claim 7, wherein, based on 100 parts by weight of the base resin, the content of the polypropylene resin is 25 to 45 parts by weight, the content of the ethylene copolymer is 30 to 55 parts by weight, the content of the maleic anhydride-grafted polyolefin resin is 10 to 25 parts by weight, and the insulating composition further comprises 2.5 to 3.5 parts by weight of a lubricant based on 100 parts by weight of the base resin. Claim 9 A non-crosslinked insulating cable according to claim 8, characterized in that the above-mentioned lubricant comprises one or more selected from the group consisting of stearic acid-based lubricants, polyethylene wax-based lubricants, and silicone-based lubricants in the form of masterbatch. Claim 10 A non-crosslinked insulated cable according to claim 6, wherein the high-melting-point polyolefin elastomer (POE) and the low-melting-point polyolefin elastomer (POE) satisfy the following mathematical formulas 2 and 3. [Mathematical Formula 2] [Mathematical Formula 3] In the above mathematical formulas 2 and 3, x1, MI1, and Tm1 are the content (g), melt index (g / 10 min), and melting point (°C) of the high-melting-point polyolefin elastomer, respectively, and x2, MI2, and Tm2 are the content (g), melt index (g / 10 min), and melting point (°C) of the low-melting-point polyolefin elastomer, respectively. Claim 11 A non-crosslinked insulated cable according to claim 1, characterized in that the flame retardant comprises a metal hydroxide flame retardant and a nitrogen-based flame retardant aid. Claim 12 A non-crosslinked insulated cable according to claim 11, characterized in that the nitrogen-based flame retardant aid comprises melamine cyanurate. Claim 13 A non-crosslinked insulating cable according to claim 11, characterized in that, based on 100 parts by weight of the base resin, the content of the metal hydroxide flame retardant is 150 to 190 parts by weight, and based on the total weight of the insulating composition, the content of the nitrogen-based flame retardant aid is 5 to 20 parts by weight. Claim 14 A non-crosslinked insulating cable according to claim 1, characterized in that the insulating composition comprises 1 to 20 parts by weight of calcium carbonate (CaCO3) as a filler based on 100 parts by weight of the base resin. Claim 15 A non-crosslinked insulating cable according to claim 14, characterized in that, based on 100 parts by weight of the base resin, the total content of the flame retardant and the filler is 150 to 200 parts by weight. Claim 16 A non-crosslinked insulating cable according to claim 1, wherein the insulating composition comprises 0.1 to 10 parts by weight of other additives based on 100 parts by weight of the base resin, and the other additives comprise one or more selected from the group consisting of antioxidants, hygroscopic agents, processing stabilizers, and pigments. Claim 17 A non-crosslinked insulated cable according to claim 1 or 2, characterized in that the insulating layer is extruded at an extrusion die temperature of 145°C or higher and an extrusion line speed of 150 mpm or higher. Claim 18 A non-crosslinked insulated cable according to claim 17, characterized in that the conductor is preheated to 115°C or higher before the extrusion of the insulating layer.
Citation Information
Patent Citations
Rubber / plastic coated wire, and method and device for manufacturing this coated wire
JP1997282952A
Propylene-based resin composition and use thereof
JP2013256670A
Non-halogen flame retardant resin composition and electric wire / cable using the same
KR1020090096714A
Halogen free flame-retardant crosslinked polyolefin insulation wire
KR1020180111710A